Efektivitas Teh Daun Katuk terhadap Produksi ASI pada Ibu Postpartum Hari ke 4-7 - Sofia Mawaddah; Novia Karlawaty (Jurnal Surya Medika (JSM), 2021)
The low coverage of exclusive breastfeeding is a challenge for midwives to be more active in promoting health about the importance of exclusive breastfeeding for infant growth. The low coverage of exclusive breastfeeding can have an impact on the quality of life for future generations of the nation and also on the national economy. One of the efforts to increase the rate of breast milk secretion and production is through the use of traditional herbal medicines such as katuk leaf tea. The aim of this study was to determine the effectiveness of katuk leaf tea. on milk production in postpartum mothers on day 4-7. This research method is a quasi-experimental post-test-only non-equivalent control group design with a sample size of 30 postpartum mothers who meet the inclusion criteria. The statistical test of this study is the independent T-test. The results showed that there was an effect of giving katuk leaf tea on increasing breast milk production in postpartum mothers with a P-Value = 0.000 (<0.05).